2008
DOI: 10.1161/strokeaha.107.489997
|View full text |Cite
|
Sign up to set email alerts
|

Linking MRI Hyperintensities With Patterns of Neuropsychological Impairment

Abstract: Background and Purpose-Leukoaraiosis (LA) might interrupt intra-and interhemispheric communication and thus induce cognitive impairments and dementia. It remains unclear, however, if there is a volume threshold of LA that is needed before either the signs of dementia and/or a specific pattern of neuropsychological impairment become manifest. Roman et al has suggested that 25% of white matter may need to be involved before white matter alterations influence the clinical signs associated with dementia. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 61 publications
1
41
0
1
Order By: Relevance
“…In patients with dementia, subcortical vascular disease is often associated with poor performance on this test (Libon et al, 2008 ;Price et al, 2005 ). Whether vascular disease is responsible for the differential impairment on executive tests in patients classifi ed as dysexecutive MCI is unknown at the present time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with dementia, subcortical vascular disease is often associated with poor performance on this test (Libon et al, 2008 ;Price et al, 2005 ). Whether vascular disease is responsible for the differential impairment on executive tests in patients classifi ed as dysexecutive MCI is unknown at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that this test is not commonly used as a measure of executive control in dementia research. However, in numerous prior studies, this test has been shown to differentiate between dementia subtypes (see Libon et al, 2001Libon et al, , 2008Price et al, 2005 ). Also, previous research using principal component analysis (PCA) with dementia patients has shown that the WMS-Mental Control AcI (Boston Revision) consistently loads with performance on tests of letter fl uency (letters "FAS") and other executive control tests (see Giovannetti et al, 2001 ;Lamar et al, 2004 ).…”
Section: Executive Systems Functioningmentioning
confidence: 99%
“…threshold studies 4,5 were repeated in the current study for comparison purposes. All neuropsychological measures were administered and scored by examiners who were blind to the imaging data.…”
Section: Neuropsychological Assessment Measures Used In Prior Lamentioning
confidence: 99%
“…приближался к СоД), в то время как на сопутствующий альцгейме-ровский процесс указывали лишь выраженная атро-фия гиппокампа и корковые ЦМК [51][52][53]. Хотя у пациентов с БА также выявлялся лейкоареоз, преи-мущественно перивентрикулярный в виде «шапо-чек» и узких «полос» по краю боковых желудочков, он не коррелировал с клинической картиной [6,11,23].…”
Section: Discussionunclassified